Polyvinyl Polymer- Based Olanzapine Nanoparticles for Transdermal Delivery: Design, In-vitro and Ex-vivo Evaluation - AL-shaibani, Abulfadhel jaber neamah; Mowafaq M. Ghareeb (Iraqi Journal of Pharmaceutical Sciences, 2025)
AbstractOlanzapine (OLZ) is classified a typical antipsychotic drug, which utilized for treatment of schizophrenia. It possesses poor water solubility and high membrane permeability, so, OLZ classified as class II according to biopharmaceutical classification system (BCS). Its oral bioavailability is (60%) due to poor solubility and extensive first-pass hepatic metabolism. Hence, the objective of this study was to prepare and evaluate the nanoparticles of OLZ for transdermal delivery. Nanoprecipitation method was employed to formulate the nanoparticles, where methanol utilized to dissolve the drug and form organic phase, which was added to an aqueous phase that consist of deionized water and stabilizer at speed of 1ml/min using syringe pump. The formulations of nanoparticles were evaluated by different characterization studies like particle size determination, polydispersity index (PDI), zeta potential, entrapment efficiency and an in vitro release of drug in order to select the optimized formula. The optimized formula was subjected for further studies such as surface morphology by field emission scanning electron microscope (FESEM) and atomic force microscope (AFM), fourier transform infrared spectroscopy (FTIR) to investigate the compatibility between drug and polymer and differential scanning calorimetry (DSC). The results of characterizations revealed that OLZ nanoparticle (OLZ-8) is selected as optimized formula, which consist of polyvinylpyrrolidone (PVP-K15) and OLZ in ratio (2:1). The characteristics of OLZ-8 were mean particle size (95.2±4.66 nm), PDI (0.282±0.18), zeta potential (-17.09 mV), entrapment efficiency (76.4±6.93) and an in vitro release of drug was higher and significant (P<0.05) as compared with other formulations and pure drug. FESEM and AFM revealed that the morphology of nanoparticle OLZ-8 was spherical in shape, also, AFM revealed that the particle size of OLZ-8 is approximate to the size that recorded by zeta sizer. FTIR studies revealed that there was a compatibility between drug and polymer. DSC results indicated that there was a decrease in crystallinity of OLZ. It can be concluded that the optimized formula OLZ-8 was regarded as a promising formula to improve the bioavailability of olanzapine when prepared as dissolving microneedle for transdermal delivery in future.